PENGARUH STRATEGI PEMBELAJARAN MIND MAPP TERHADAP PEMAHAMAN KONSEP PADA MATERI SISTEM EKSKRESIKELAS XI IPA SMA NEGERI 1 PAMPANGAN OKI - Muhammad Isnaini; kurratul aini; rani angraini (Bioilmi: Jurnal Pendidikan, 2016)
This study aims to look the effect of learning Mind Mapp strategies towards students understanding concept of excretory system to the XI IPA class at SMAN 1 Pampangan OKI. The variable in this study is learning Mind Mapp strategy as independent variables and the understanding of concept as dependent variable. The sample was XI IPA 3 and XI IPA 2 as experimental class and class XI IPA 1 as the control class. Grade students the method used in this study is an experimental method, while the techniques data collecting used is a written test and test of understanding with Mind Mapp rubric assessment. Written test is used to see how the students ability of understanding the concept after applied learning Mind Mapp strategies. Tests of understanding with the Mind Mapp rubric assessment used to see how students understanding ability to create Mind Mapp. The analysis data using t-test with significance level of 5%. Based on the data hypothesis testing control class and experimental class of the obtained value of 0.000 < 0.05, significantly different. The students Mind Mapp score overall can be said very good, with the average score 84.81. It can be concluded that there is significant influence of application Mind Mapp learning strategies to the students understanding concept with the material excretory system to the XI IPA class at SMAN 1 Pampangan OKI. Keywords: Learning Mind Mapp Strategies; Students Understanding Concept; Excretion system.